PENERAPAN MITIGASI RISIKO DALAM PENGAMBILAN KEPUTUSAN UNTUK PEMILIHAN PROGRAM STUDI DI PERGURUAN TINGGI - Ikhwan Rahmatika Latif; Karuni Humairah Arta; Ilham Mirza Saputra; Desi Marlizar; Nizar Saputra (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
Risk mitigation is a strategic approach that aims to reduce or maintain the initial level of risk until it reaches a desired residual level. The main purpose of this skill is to equip students with the necessary abilities to effectively overcome obstacles that arise after high school studies. The method of implementing this service is by socialization, education, and evaluation related to Risk Mitigation in decision-making management carried out at SMA Negeri Unggulan Tapaktuan. Participation in this community service activity produces and makes students able to practice risk mitigation in decision-making management for the benefit of students in determining the study program and campus of their choice after senior high school studies. Participants of the activity understand the importance of knowing their interests and talents for the basis of decision making to choose a study program in college. Errors in making study programs can be prevented through analysis of academic grades obtained at school.